Profile of paediatric occupational therapy practice in Eastern Mediterranean countries - Zainab A. Jasem (Scandinavian Journal of Occupational Therapy)
Background Paediatric occupational therapy (OT) is considered the largest practice area in OT in several regions, including the Eastern Mediterranean (EM) countries.Aims/objectives This study aimed to establish a profile of paediatric occupational therapists in EM countries to identify theoretical models, assessments and interventions employed. It also investigated the therapists’ usage of evidence-based practice in their practice.Material and methods We conducted a cross-sectional survey using a questionnaire which was distributed electronically to occupational therapists working with children.Results The participants included 118 therapists. Majority of the participants were working at rehabilitation centres. The primary client groups were pre- and school-age children with autism spectrum disorder and cerebral palsy. The most frequently used assessments were sensory-related tools. Activities of daily living and play were the most often targeted interventional area. Participants highlighted some of the challenges faced in implementing evidence in their practice.Conclusion Paediatric occupational therapists are usually exposed to specific age groups and conditions. However, a lack of knowledge practice in some areas and challenges in others exist.Significance Within the EM region, knowledge regarding therapists’ practices is lacking. Actions should be taken to improve current practice and meet the current needs of clients, and utilise evidence-based practices.